Insights on the therapeutic use of ivermectin: Mechanism of action and histopathological effects - Abou El-Fetouh, Moustafa S.; Elseddawy, Nora M.; Abdelsamia, Hagar M. (Journal of Advanced Veterinary Research, 2024)
Ivermectin is a broad-spectrum antiparasitic drug with outstanding efficacy and a wide margin of safety. This drug has been widely utilized in veterinary medicine since 1987, and its use in humans has grown. Ivermectin is a broad-spectrum anti-parasitic agent licensed by the FDA. Ivermectin is a mixture of 80% or more avermectin B1a (AB1a) analogue and 20% or less avermectin B1b analogue. Iverzine has been proven to have widespread antiviral action in recent years. Ivermectin has also a broad-spectrum activity against the viruses that cause dengue, Zika, HIV, and yellow fever in vitro. Despite this in vitro action, no clinical trials have shown that ivermectin has a therapeutic benefit in patients with these viruses. Some ivermectin studies have also revealed potential anti-inflammatory qualities, which may be beneficial in persons with COVID-19. However, the use of ivermectin in animals was also associated with some histopathological effects in the internal organs including the liver, kidney, spleen, and brain. The purpose of this review was to provide light on the mechanism of action of ivermectin and its related histopathological consequences in various animal species.